Critical Thinking an Antidote to Artificial Intelligence Threat: An Innovation in Teacher Education Practices: AN INNOVATION IN TEACHER EDUCATION PRACTICES - Xusheng, Qian; Komolafe, Blessing Funmi (Proceedings of the International Conference on Education, 2020)
The role of Critical thinking skill in developing 21st-century teaching profession can’t be overstated. Projecting into the future, critical thinking is expected to serve as tools for integrating Artificial Intelligence into the teaching profession as well as an antidote to the threats of artificial intelligence to the teaching profession in the machine learning age. This study investigates John Dewey’s philosophy on critical thinking and reviews existing literature on the teaching profession. The questions raised by this study include: what is critical thinking requirement skill in 21st century? Does critical thinking serve as a means of integrating artificial intelligence (AI) into the teaching profession? What is the basic critical thinking skill and strategies needed for effective teaching that serves as an antidote to AI threats? The results imply that teachers need to acquire critical skills in order to outsmart machine, which has become a threat to many professions including teaching. The relevant teacher is one that does not function like a programmed machine. Ability to think critically is the answer to the “Austria vision 2030”( Machine learning age), teachers need to think critically in the teaching profession innovation as a major means to overcome AI threat and in order to be relevant in 21st-century machine learning age.